Fundusze venture capital - źródło finansowania inwestycji małych i średnich przedsiębiorstw - Daszyńska-Żygadło, Karolina (Venture Capital - Source of Financing Investments of Small and Medium Enterprises, 2005)
Dynamically acting, innovational enterprise belonging to the sector of SME's is aware of the necessity of continuous investing which means keeping up to the technical and technological progress. According to that, sources of financing business activities cannot only originate from the detained profit. Potential sources of financing investment activities of small and medium enterprises are venture capital funds. The aim of this elaboration is to present the possibilities of using this kind of financing by SME's. It shows the whole process of cooperation with venture capital - starting from making the decision of using venture capital funds by the enterprise and ending at finishing the cooperation with venture capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 128-139